Is there a beneficial effect of a high-protein diet on body composition and strength capacity in physical active middle-aged individuals?—An eight-week randomized controlled trial - Schalla, Jan; Frommelt, Sina; Geisler, Stephan; Isenmann, Eduard (Frontiers in Sports and Active Living, 2024)
Introduction: Demographic changes are resulting in a continual increase in the proportion of individuals over 65 years old. Simultaneously, muscle mass (MM) tends to decrease with age, with a decline noticeable from the middle of the fourth decade of life. While physical activity is considered a modulator for maintaining MM, the interaction with nutrient uptake, especially protein intake, is getting more into focus. Due to a lack of data on the effect of a high-protein diet on middle-aged individuals (40-65 years), this study aimed to investigate the influence of a high-protein diet in middleaged physically active persons on body composition and performance.Methods: Using stratified randomization, participants were allocated to either a high-protein group (>2.3g/kg FFM/day) (n=12, age=57.83±7.74years, height=170.42±11.04cm, BMI=30.26±4.46, MM=31.71±6.89kg) or a control group (<2.3g/kg /FFM/day) (n=14, age=58.21±6.44years, height=170.57±8.28cm, BMI=26.31±5.59, MM=29.67±8.08kg). Body composition (fat-free mass (FFM), fat mass (FM), MM) and strength were assessed at baseline (T0), after four weeks (T1) and after eight weeks (T2). Exercise habits were not changed over the entire period and dietary habits were recorded using FDDB Explorer. Statistical analysis was performed using the current version of R and linear mixed models.Results: No significant differences in energy intake were found between the groups (p=.974). In macronutrient distribution, a significantly higher consumption of protein was found in the high-protein group (p<.0001, d=2.22) (140±70g/day [HPG] vs. 79±40g/day [CG]). A trivial reduction in FM over time in both groups (p=.046, d=0.04, ∆𝐭=-.83±1.60kg) was observed. No significant differences were detected in FFM (p=.887) and MM (p=.711). Trivial interaction effects (time*group) were observed for upper (p=.007, d=0.12, ∆HPG=4.38±3.25kg) and lower body strength (p=.0507, d=0.07, ∆HPG = 3.33±2.36kg).Our results indicate no to only trivial effects of adding a high-protein diet to otherwise physically active individuals. Trivial effects could be seen for an increase in muscle strength after this 8-week intervention. However, MM and FFM were not significantly affected. Based on the small effect sizes we observed in our results we do not see a benefit of a high-protein diet on body composition and strength capacity without altering the exercise habits.